Agent-based simulation of a project fractal company - Canavesio, Mercedes M. (2016)
In response to competitive pressures small and medium enterprises have begun to form alliances between them. This allows each company to increase their ability to react and adapt to changes in their business environment, concentrating on their core competencies, increase the availability of resources and gain economies of scale. Thus, the project-based fractal company model enables virtual and temporary integration between different companies to achieve specific business objectives. The successful implementation of the model lies in the establishment of client-server relationships between project managers. This paper analyses the use of agentbased simulation to show behaviors that emerge from the interaction of project managers and resources managers when they establish client-server relationships. To do this, use Netlogo language as a tool intends to demonstrate emergent behavior resulting from interactions between agents of the fractal company.